Pleonexes Spence Bate, 1857 (Amphipoda: Ampithoidae) in the Persian Gulf and the Gulf of Oman - Momtazi, Farzaneh; Maghsoudlou, Abdolvahab (Zootaxa, 2020)
A new species of ampithoid amphipod, Pleonexes nargessi, is described from the southern Iranian coasts of the Persian Gulf and the Gulf of Oman. The new species is the most similar to P. kava (Myers, 1985), but distinguished by the presence of the posterior tooth and the defining robust seta on the palm of male gnathopod 1, semi prehensile pereopod 5, and non-prehensile pereopods 6–7. Ampithoe qeshmensis Layeghi & Momtazi, 2018 is transferred into Pleonexes.